Husein Muhammad antara Feminis Islam dan Feminis Liberal - Susanti, Susanti (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2014)
This article focuses on the discussion about Hussein Muhammad?s thought related to the empowerment of women. Hussein is aware of the oppression in interpretation related to understanding about women. Husein is also fully aware of the role of religion and religious experts in such oppression and subordination against women. According to Hussein, women and men are equal before God as His servants. There is no such superiority among them before God except by their piety. It implies that the assumption which sees women as ?the complementary creature? and places them only in domestic sphere is not true. Women also have their contribution to khilâfah on earth and they also have the same duty to commanding the good and forbidding the evil. Women can freely determine which path to choose, either to become merely a housewife or to be a career woman to earn a living. This is because every woman has different economic situation. Therefore, it is permissible for women to work to gain wealth for the sake of her life and her family.